2013
DOI: 10.4103/1305-7456.119077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bolton analysis and tooth size measurements obtained using conventional and three-dimensional orthodontic models

Abstract: Objectives:The aim of this study was to compare the accuracy, reproducibility, efficacy and effectiveness of measurements obtained using digital models with those obtained using plaster models.Materials and Methods:A total of 20 digital models were produced by the Ortho Three-dimensional Models (O3DM) Laboratory and their software (O3DM version 2) was used to obtain measurements. Identical plaster models were used to obtain measurements of teeth with a vernier caliper. The maximum mesiodistal width of each stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
0
26
0
2
Order By: Relevance
“…Currently, with the advent of intraoral and dental cast scanners, this analysis may be digitally performed, using several softwares in a faster and simpler manner, with scientifically demonstrated accuracy. 30 - 32 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, with the advent of intraoral and dental cast scanners, this analysis may be digitally performed, using several softwares in a faster and simpler manner, with scientifically demonstrated accuracy. 30 - 32 …”
Section: Discussionmentioning
confidence: 99%
“…New scanning products and software introduced to the market should continue to be investigated to determine their clinical accuracy and reliability. Several studies have reported clinically acceptable Bolton analysis performed with OrthoCad (Cadent Inc., Carlstadt, NJ, USA), 15 20 and Nalcaci et al 21 concluded that Bolton analysis performed with Ortho 3D Models (O3DM; ORTHOLAB, Sp, ZO.o., Częstochowa, Poland) can be reliably used in the clinical setting. The present study is the first to verify the clinical accuracy of Bolton analysis using the Ortho Insight 3D system.…”
Section: Discussionmentioning
confidence: 99%
“…[33] The precision of digital impression has been studied by several researchers and found out that use of digital models is a relatively new technique that has an accuracy of up to 10 µm, and the models have been found to be as reliable as traditional stone casts. [34] Nalcaci et al [35] found out statistically significant differences between measurements obtained for width of 6 anterior teeth and 12 overall teeth using plaster and digital models; however, these differences were not within the clinically significant range (~0.27-0.30 mm). Therefore, casts are scanned using digital scanner for conventional technique.…”
Section: A N U F a C T U R I N G P R O C E S S O F R E M O V A B L mentioning
confidence: 99%